Silent cinema and the politics of space - Bean, Jennifer M., 1968-; Kapse, Anupama; Horak, Laura (Bloomington, Indiana : Indiana University Press, 2014)
In this cross-cultural history of narrative cinema and media from the 1910s to the 1930s, leading and emergent scholars explore the transnational crossings and exchanges that occurred in early cinema between the two world wars. Drawing on film archives from around the world, this volume advances the premise that silent cinema freely crossed national borders and linguistic thresholds in ways that became far less possible after the emergence of sound. These essays address important questions about the uneven forces-geographic, economic, political, psychological, textual, and experiential-that un.
Introduction / Jennifer M. Bean -- Picturing Space. Introduction / Anupama Kapse -- Location, "Location": On the Plausibility of Place Substitution / Mark B. Sandberg -- Insurgent Place as Visual Space: Location Shots and Rival Geographies of 1857 Lucknow / Priya Jaikumar -- Prints in Motion. Introduction / Jennifer M. Bean -- An Afterlife for Junk Prints: Serials and other 'Classics' in late 1920s Tehran / Kaveh Askari -- Robespierre Has Been Lost: D.W. Griffith's Movies and the Soviet Twenties / Yuri Tsivian -- Translations and Transportation: Toward a Transnational History of the Intertitle / Laura Isabel Serna -- Impertinent Appropriations Introduction / Anupama Kapse -- From "Misemono" to Zigomar: A Discursive History of Early Japanese Cinema / Aaron Gerow -- The Crisscrossed Stare: Chinese Protest and Propaganda in the Not-So-Silent Era / Yiman Wang -- Around the World in 80 Minutes: Douglas Fairbanks and the Indian Stunt Film / Anupama Kapse -- Cosmopolitan Sexualities and Female Stars. Introduction / Jennifer M. Bean -- National Soul/Cosmopolitan Skin: Swedish Cinema at a Crossroads / Jan Olsson -- Queer Crossings: Greta Garbo, National Identity, and Gender Deviance / Laura Horak -- Cosmopolitan Women: Marlene Dietrich, Anna May Wong, and Leni Riefenstahl / Patrice Petro.
Includes bibliographical references.
Print version record.
JSTOR
Keywords: Silent films -- History and criticism; Space in motion pictures; Films muets -- Histoire et critique; Espace au cinéma.; PERFORMING ARTS -- Reference; PERFORMING ARTS -- Film & Video -- History & Criticism; Silent films; Space in motion pictures; Criticism, interpretation, etc